Pattern and Outcome of Otolaryngological and Facial Injury in Road Traffic Accidents at a Tertiary Care Centre in Eastern Nepal - Thakur, Sanjeev Kumar; Aryal, Gyan Raj; Thakur, Rishikesh; Ghimire, Nisha (Birat Journal of Health Sciences, 2023)
Introduction: Otolaryngological trauma is prevalent in road traffic accidents (RTA), with or without multiple organ injuries.Objective: The aim was to report the number and pattern of otolaryngological injuries in cases of road traffic accidents (RTA) and their outcome.Methodology:  A prospective study over one year of cases of RTA was done. The pattern and outcome of the otolaryngological and facial injury was recorded.Result: Out of 90 cases, 69(76.66%) were male, 21 (23.33%) were female. The mean age was 32.33 ±13Yrs.The mean time of presentation to emergency was 16.24 ±19.61hrs. Motor vehicle accident was more common, 75 (83.33%). Multiple injury was found in 68(75.55%) cases. Among 89 cases with ear problem, common complaints were hearing loss, 20(22.47%), otalgia, 17(19.1%) and laceration of pinna 13(14.6%). Ear complications were seen in16 (17.97 %) cases . Among 55 cases of nose/face injury, common presentation were epistaxis, 20 (36.36%) and nasal bone fracture, 12 (21.81%).  Nasal complications were found in 8 (14.54%) cases. In 32 cases of neck/throat trauma, laceration was found in 11 (34.37%) cases. 4(12.5%) cases had undergone tracheostomy.  Complications (stenosis and hoarseness) were found in 6(18.75%) cases. Patients who required admission were 81(90%).Conclusion: Motor vehicle accidents were more common. It was commoner in male. Ear was most commonly affected by injury and complications.  The complication of nose and neck/throat was associated with prolonged admission.